ANALISIS TOWS MATRIKS TERHADAP FINANCIAL TECHNOLOGI PEER TO PEER LENDING BERBASIS SYARIAH DI INDONESIA - Zuhri, Nurhadi (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
The development of peer-to-peer (P2P) lending fintech in Indonesia is progressing rapidly. The development of Sharia-based P2P lending fintech itself is influenced by various external and internal factors. The TOWS matrix analysis is employed in this research to analyze and connect different factors and mitigate the appropriate strategies. The research adopts the descriptive qualitative research method, utilizing secondary data and the documentation method for data collection. The results combine external factors, such as challenges (threats) and opportunities (opportunities), with internal factors, namely weaknesses (weaknesses) and strengths (strengths), to explain the T-W strategy, which involves minimizing weaknesses to overcome threats, the O-W strategy, which utilizes opportunities to address weaknesses, the T-S strategy, which tackles threats by leveraging strengths, and the O-S strategy, which seizes better opportunities by utilizing existing strengths.